2019
DOI: 10.3390/cancers11030399
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Treatment in Resectable Gastric Cancer: Current Perspectives and Future Directions

Abstract: Gastric cancer (GC) is the fifth-most common cancer worldwide and an important cause of cancer-related-death. The growing knowledge of its molecular pathogenesis has shown that GC is not a single entity, but a constellation of different diseases, each with its own molecular and clinical characteristics. Currently, surgery represents the only curative approach for localized GC, but only 20% of patients (pts) showed resectable disease at diagnosis and, even in case of curative resection, the prognosis remains po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 71 publications
(123 reference statements)
0
38
0
Order By: Relevance
“…However, the specific regimens for GSRC remain uncertain. 41,42 Several studies and retrospective analyses have shown that GSRC cannot benefit from chemotherapy or radiotherapy due to chemoresistance. 6,8,10 Chemotherapy GSRC has the characteristic of chemoresistance which has been confirmed by several studies.…”
Section: Adjuvant and Neoadjuvant Treatmentsmentioning
confidence: 99%
“…However, the specific regimens for GSRC remain uncertain. 41,42 Several studies and retrospective analyses have shown that GSRC cannot benefit from chemotherapy or radiotherapy due to chemoresistance. 6,8,10 Chemotherapy GSRC has the characteristic of chemoresistance which has been confirmed by several studies.…”
Section: Adjuvant and Neoadjuvant Treatmentsmentioning
confidence: 99%
“…1 These tumors are difficult to find because their early symptoms are not obvious, and most of these tumors would have already progressed to the late stage with lymphatic or distal metastasis by the time they are discovered. 2 Thus, simple surgical treatment cannot aid in full eradication of these tumors. To date, combinational chemotherapy forms the main part of the treatment strategy for advanced gastric cancer with less than 10% of 5-year survival rate.…”
Section: Introductionmentioning
confidence: 99%
“…In 2018, there were approximately 1.03 million new cases of GC globally and about 0.78 million deaths occurred because of GC [1]. Surgery-based comprehensive treatment is currently the main treatment approach for GC [2]. However, the postoperative 5-year survival rate of GC patients is relatively low.…”
Section: Introductionmentioning
confidence: 99%